Efesiensi Anggaran Pemerintahan Presiden Prabowo; Implementasi Prinsip Transparansi dan Akuntabilitas Sesuai Pasal 10 Undang-Undang Nomor 30 Tahun 2014 Tentang Administrasi Pemerintahan (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2025)
This study aims to analyze the efficiency of the government budget under President Prabowo's leadership, focusing on the implementation of the principles of transparency and accountability as stipulated in Article 10 of Law Number 30 of 2014 concerning Government Administration. The method used in this study is normative juridical, which involves the study and analysis of various written legal materials, including laws, government regulations, and court decisions. The data analyzed are secondary data. The findings of this study indicate that in the context of good governance, transparency and accountability are key components to ensure that the management of the state budget is effective, efficient, and accountable to the public. However, to achieve optimal efficiency, a stronger commitment is needed from all parties involved, including legislative institutions and civil society. In addition, this study emphasizes that the implementation of the principles of transparency and accountability is not only important for increasing budget efficiency, but also for building public trust in the government. Keywords: Accountability, Budget Efficiency, Transparency, Law No. 30 of 2014 concerning Government Administration.